JSE 27:3 Editorial - Braude, Stephen (Journal of Scientific Exploration, 2013)
In these editorials I prefer not to revisit issues I’ve covered before, much less recycle previous editorials. But the recent Michigan conference of the SSE has convinced me that the time may have arrived. What provoked me was this. On several occasions I happened to overhear attendees making confidently dismissive remarks about what they took to be the extreme or outlandish views and presentations they’d encountered during the conference. And I was reasonably certain that many of those expressing these opinions did so with little or no justification for the certitude they displayed. With that in mind, I submit again, with a few suitable updates, some remarks I made back in Volume 23. It’s not often that I get to feel like a spokesperson for empirical conservatism. But that happened when I was invited to give a talk at the 50th Annual Conference on Anomalous Phenomena sponsored by the International Fortean Organization (INFO). The occasion provided several healthy illustrations about what I suppose we can call boggle relativity. The conference was stimulating, challenging, and professionally run, and I was happy to meet quite a few very smart and pleasant attendees.